Feminisms in Kazakhstan: On the intersection of global influences and local contexts - Udod, Xeniya (Nazarbayev University School of Sciences and Humanities, 2018)
This thesis is an exploratory qualitative study into the recent revival of feminism which is now gaining its momentum in Kazakhstan, where several feminist unions and numerous individual activists publicly promote feminist ideas, advocate for gender equality and LBTIQ rights in the country. By drawing on in-depth interviews with the outspoken feminist activists, I posit that contemporary feminisms in Kazakhstan are now entering the stage of reflecting on their specific stance vis-à-vis the complex set of gender ideologies and practices concerning Central Asian women and their space in the society, ranging from (but not limited to) the system of patriarchy, controversial Soviet project of “women’s liberation,” more recent influences of Western neoliberalism and capitalism, and the dominant discourse of “Western feminism.” My research data demonstrate that by admitting the constructed, complex nature of contemporary Kazakhstani feminisms, my respondents move to the elaboration on the modalities of the movement’s further prospects, such as its grounding in Kazakh(stani) context, as well as closer collaboration with other Central Asian feminisms which has the potential to form a particular local type of post-socialist feminisms, sensitive to and embedded in the region’s tangled geotemporal realities...
Keywords: feminism; Central Asian women; Kazakhstani feminisms